Vol.2 - "Shastri, Yajneshwar S. (ed.)" (Delhi, 2006)
The Department of Philosophy Guajarat University Ahmedabad organized a five-day International Conference on World Peace from 20th Dec. 2003 to 2nd Jan 2004 in which more than 240 delegates from all over the world participated. In the conference's academic sessions that ran simultaneously at seven places, scholars presented more than 210 papers from various fields.
Keywords: World peace